Risiko Introduksi Gandum ke Timor Tengah Utara: Penyakit Hawar Daun dan Busuk Batang - Aloysius Rusae; Efi Toding Tondok; Suryo Wiyono (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2015)
Wheat has a great potency to be cultivated in Timor Tengah Utara (TTU). However, disease is one of the risks for introduction of wheat. The existence of wheat disease in TTU is unknown because wheat has never been grown in this area. This study aims to determine the potential risks of major diseases that will infect wheat plants when introduced to the TTU. The methods used in this study consisted of wheat cultivation in the field, followed by observation and identification of the main diseases on wheat. Wheat varieties grown in field were Dewata, Selayar and Nias. Koch’s postulate were performed to identify the suspected microbes as pathogens. Morphological-based identification was applied on the isolated pathogens. The main diseases on wheat cultivated in TTU were leaf blight and stem rot. The results of Koch’s postulate showed that Helminthosporium gramineum was the causal of leaf blight and Rhizoctonia sp. was the causal of stem rot. Disease incidence reached 82–93% and 11–22% for leaf bligh and stem rot disease, respectively. Disease severity of leaf blight and stem rot disease on var. Dewata was the lowest compared to var. Selayar and var. Nias.